2021
DOI: 10.11609/jott.6319.13.3.17918-17929
|View full text |Cite
|
Sign up to set email alerts
|

An annotated checklist of amphibians in and around Dampa Tiger Reserve, Mizoram, India

Abstract: Amphibians are an integral part of the ecosystem and act as an ecological indicator.  As several species are added to the list of threatened species every year due to loss of habitat, it is important to understand the role of unmanaged landscape for sustenance of amphibian diversity.  In this study, 28 amphibian species were recorded from different modified habitat including 19 new records for Dampa Tiger Reserve (DTR) and its surrounding areas.  Further, six species, Amolops indoburmanensis, Limnonectes khasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Mizoram is an important part of the Indo-Burma biodiversity hotspot, as it contains a diverse flora and fauna. Studies within the last decade have revealed new records of amphibians in the state (e.g., Chaitanya et al 2017;Lalremsanga 2017aLalremsanga , 2017bLalremsanga , 2017cLalbiakzuala and Lalremsanga 2019;Decemson et al 2020Decemson et al , 2021Kundu et al 2020;Lalremsanga et al 2020Lalremsanga et al , 2021aLalremsanga et al , 2021bMalsawmhriatzuali et al 2020;Muansanga 2020;Muansanga et al 2020Muansanga et al , 2021aMuansanga et al , 2021b. Additional surveys combined with more stable systematics are likely to identify additional species in the region.…”
Section: Discussionmentioning
confidence: 99%
“…Mizoram is an important part of the Indo-Burma biodiversity hotspot, as it contains a diverse flora and fauna. Studies within the last decade have revealed new records of amphibians in the state (e.g., Chaitanya et al 2017;Lalremsanga 2017aLalremsanga , 2017bLalremsanga , 2017cLalbiakzuala and Lalremsanga 2019;Decemson et al 2020Decemson et al , 2021Kundu et al 2020;Lalremsanga et al 2020Lalremsanga et al , 2021aLalremsanga et al , 2021bMalsawmhriatzuali et al 2020;Muansanga 2020;Muansanga et al 2020Muansanga et al , 2021aMuansanga et al , 2021b. Additional surveys combined with more stable systematics are likely to identify additional species in the region.…”
Section: Discussionmentioning
confidence: 99%
“…was originally described from Hathazari, Chittagong District, Bangladesh, and later recorded from Dhaka District, Bangladesh (Sarker et al 2012), and Nazipur, Rajshahi Division, Naogoan District, Bangladesh (Ahmad and Alam 2013). In India, the species has been recorded from Aizawl District (Lalronunga et al 2017) and the Dampa Tiger Reserve, Mamit District (Decemson et al 2021), in Mizoram. The conservation status of this species has not been assessed for the IUCN Red List of Threatened Species (Dinesh et al 2020).…”
Section: Reptiles and Amphibians C O N S E R V At I O N A N D N At U R A L H I S T O R Ymentioning
confidence: 99%
“…The genus Hydrophylax consists of four currently recognized species of which the Assam Forest Frog (Hydrophylax leptoglossa) occurs in the northeastern Indian states of Assam, Tripura, Meghalaya, and Mizoram (Frost 2021). In Mizoram, the species has been reported previously from the Dampa Tiger Reserve in Mamit District (Pawar and Birand 2001;Decemson et al 2021), and from Kolasib District (Lalremsanga et al 2007).…”
Section: T a B L E O F C O N T E N T S F E A T U R E A R T I C L E Smentioning
confidence: 99%